Food abundance as an environmental cue for the start of reproduction of Elaenia albiceps - Gorosito, Cristian Andrés (2020)
The time of the year when birds reproduce has a great impact on their reproductive success. That is, if they reproduce when food availability for their nestlings is low, their survival could be reduced. Therefore, birds should synchronize the maturation of their gonads with the most favorable environmental conditions for reproduction. Photoperiod length is the main cue that birds use to achieve this synchronization. However, using other cues, such as food abundance, is necessary to refine the most suitable moment for reproduction. The aim of this work was to study the synchronization between the food types consumed by the migratory Elaenia albiceps and its reproduction. The effects of ripe fruit, arthropods and caterpillar abundances on the breeding intensity of this species were evaluated. Ripe fruit and caterpillar abundances were the food resources that had the greatest effects on the number of nests with eggs. These items could constitute important food sources for the preparation of reproduction in adults, providing protein and calcium for egg formation. Ripe fruit abundance also had a great effect on the number of nests with nestlings. It was observed a synchronization between the moment of maximum abundance of this food resource and the maximum abundance of nests with nestlings. Ripe fruits have a high antioxidant and calcium content, thereby they would be beneficious for nestling growth. Hence, ripe fruit abundance would be the main cue to refine the start of reproduction of E. albiceps in Patagonian forests.